Orphaned wells, oil assets, and debt: the competing ethics of value creation and care within petrocapitalist projects of return. (12th March 2019) - Wood, Caura
Abstract: This essay explores the phenomenon known as 'orphaned wells', meaning unprofitable oil and gas wells ('legacy wells') that have become disentangled from their corporate owners owing to insolvency, or owing to a failure to comply with local regulations. Drawing from an ethnographic example of a near‐insolvent oil and gas corporation in Alberta, Canada, and its strategies of refinancing, the essay explores how value creation and the moral force of the obligation to create a financial return give rise to a 'durational ethics' that shapes corporate and financial performativities and prolongs the 'life' of legacy oil and gas assets. Legacy assets, understood as potential orphans, are thus caught up in a lively corporate practice of asset circulation and recombination often deployed by producers for the moral work of 'cleaning balance sheets'. This essay calls for 'thinking with orphans' to recognize the competing ethical registers which produce them in addition to the growing need for responsibility and corporate care for legacy oil and gas assets.